Metabolic effects of quercetin on inflammatory and autoimmune responses in rheumatoid arthritis are mediated through the inhibition of JAK1/STAT3/HIF-1α signaling - FengQi Zhang; YiYang Zhang; JiaWang Zhou; Ying Cai; ZhiYu Li; Jing Sun; ZhiJun Xie; GuiFeng Hao (BMC, 2024)
Abstract Background Rheumatoid arthritis, a chronic autoimmune disease, is characterized by synovial hyperplasia and cartilage erosion. Here, we investigated the potential mechanism of action of quercetin, the main component of flavonoids, in treating rheumatoid arthritis. Object To examine the anti-arthritic effects of quercetin and elucidate the specific mechanisms that differentiate its metabolic effects on autoimmune and inflammatory responses at the synovial cell level. Methods We created a collagen-induced arthritis (CIA) model in Wistar rats, which were administered quercetin (50 or 100 mg/kg) continuously for four weeks via stomach perfusion. The arthritis score, histopathological staining, radiological assessment, and serum biochemical parameters were used to study the impact of quercetin on disease improvement. Additionally, immunofluorescence was employed to detect JAK1/STAT3/HIF-1α expression in rat joints. Moreover, the effects of quercetin (20, 40, and 80 µmol/L) on the properties and behavior of synovial fibroblasts were evaluated in an in vitro MH7A cell model using flow cytometry, CCK8, and transwell assays. Further, the mRNA expression levels of inflammatory cytokines IL1β, IL6, IL17, and TNFα were assessed by quantitative real-time PCR. Glucose, lactate, lactate dehydrogenase, pyruvate, pyruvate dehydrogenase, and adenosine triphosphate assay kits were employed to measure the metabolic effects of quercetin on synovial fibroblasts. Finally, immunoblotting was used to examine the impact of quercetin on the JAK1/STAT3/HIF-1α signaling pathway in synovial fibroblasts. Results In vivo experiments confirmed the favorable effects of quercetin in CIA rats, including an improved arthritis score and reduced ankle bone destruction, in addition to a decrease in the pro-inflammatory cytokines IL-1β, IL-6, IL-17, and TNF-α in serum. Immunofluorescence verified that quercetin may ameliorate joint injury in rats with CIA by inhibiting JAK1/STAT3/HIF-1α signaling. Various in vitro experiments demonstrated that quercetin effectively inhibits IL-6-induced proliferation of MH7A cells and reduces their migratory and invasive behavior, while inducing apoptosis and reducing the expression of the pro-inflammatory cytokines IL1β, IL6, IL17, and TNFα at the mRNA level. Quercetin caused inhibition of glucose, lactate, lactate dehydrogenase, pyruvate, and adenosine triphosphate and increased pyruvate dehydrogenase expression in MH7A cells. It was further confirmed that quercetin may inhibit energy metabolism and inflammatory factor secretion in MH7A cells through JAK1/STAT3/HIF-1α signaling. Conclusions Quercetin's action on multiple target molecules and pathways makes it a promising treatment for cartilage injury in rheumatoid arthritis. By reducing joint inflammation, improving joint metabolic homeostasis, and decreasing immune system activation energy, quercetin inhibits the JAK1/STAT3/HIF-1α signaling pathway to improve disease status.